Examining the Quality Enhancement and Antioxidant Properties of White Compound Chocolate Formulated with Pineapple Powder (Ananas comosus L.) - Dimas Rahadian Aji Muhammad; Arina Nur’aini; Ardiba Rakhmi Sefrienda; Siswanti Siswanti; Asri Nursiwi; Joel Garcia Juvinal (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2026)
Efforts to enhance the antioxidant activity of white compound chocolate, a type of chocolate with the lowest phenolic content, can be achieved by incorporating additional fruit-based active ingredients. Pineapple powder is a promising ingredient for chocolate formulation due to its distinctive flavor characteristics and potential bioactive compounds. This study aimed to investigate the effects of varying pineapple powder concentrations and grinding durations on the physical and chemical properties of white compound chocolate formulated with pineapple powder. The study utilized a factorial completely randomized design (CRD) with 2 factors: pineapple powder concentration (15%, 20%, and 25%) and the grinding duration (2.5, 5, and 7.5 hours). The experiment was conducted in triplicate. The results indicated that L* was significantly reduced with the addition of 20% and 25% pineapple powder. At the same time, chocolate hardness was significantly higher than the control, especially with the 25% pineapple powder addition and grinding times of 5 and 7.5 hours. The incorporation of pineapple powder increased the moisture content of the chocolate from 1.3 to 2%. Volatile compounds, such as δ-Caprolactone, benzyl valerate, benzaldehyde, 2,4-dihydroxy-, γ-Decalactone, 5-hydroxymethylfurfural, were detected in the formulated chocolate. Incorporating 25% pineapple powder increased phenolic and flavonoid content by almost fourfold. Thus, it significantly improved the antioxidant activity of the chocolate in terms of DPPH and ferric reducing antioxidant power (FRAP). Variations in grinding duration did not significantly affect the physical and chemical properties. The results of this study create new opportunities for the food industry to develop innovative chocolate variants.